Prevalence of metabolic syndrome in preeclampsia - Beigh, Mehbooba; Naik, Muzafar; Tali, Irshad; Ara, Rifat; Malik, Anjum (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preeclampsia is associated with increased morbidity and mortality and it increases with severity of preeclampsia. Preeclampsia shares many characteristics of metabolic syndrome (MeS) which has led many investigators to elucidate this relationship. The aim and objective of this study was to assess the prevalence of MS in preeclampsia and its relation with its severity. Methods: The study included 130 cases (41 gestational hypertension (GHTN), 27 mild pre-eclampsia (Mild PET), 47 severe preeclampsia (Severe PET), 13 pre-eclampsia superimposed on chronic hypertension (PSHTN) and 2 eclampsia) based on pre-specified maternal characteristics according to ACOG criteria after 20 th week of gestation. Two hundred normotensive pregnant females served as controls. The frequency of MS was assessed using pregnancy adaptation of MeS definition of the NCEP-ATP III criteria in cases and controls. Results: Metabolic syndrome was found in 37.7% of preeclampsia group and 12% of control group (p<0.00). Among the components of MeS, preeclampsia group was having significantly higher sugars (30% Vs 20%) and body mass index (BMI) (23.8% Vs 7.5%) than controls. GHTN was seen in 31.5%, mild PET in 20.8%, severe PET in 36.2%, PSHTN in 10% and eclampsia in 1.5% of cases. MeS was seen in 57.4% of severe PET, 50% of eclampsia, 26.8% of GHTN, 25.9% of mild PET and 23.1% of PSHTN. The clinical course in preeclampsia with MeS was complicated by IUD (intrauterine death), IUGR (intrauterine growth retardation), preterm delivery, APH and pulmonary edema. Oligohydromnios was less common in preeclampsia with MeS. Conclusions: The frequency of MeS was higher in preeclampsia group as compared to normotensive group. MeS was more significantly higher in patients with severe preeclampsia. In our study there were no demographic, clinical and laboratory predictors of MeS in preeclampsia. On the other hand, preeclampsia patients with MeS had significant maternofoetal complications. There is a need to screen for MeS in pregnant females from the first antenatal visit in order to predict severe preeclampsia.